2011
DOI: 10.1002/cpe.1802
|View full text |Cite
|
Sign up to set email alerts
|

A concurrent key exchange protocol based on commuting matrices

Abstract: SUMMARYIn this paper, we suggest a cryptographic protocol for symmetric key exchange based on a set of m commutative square singular matrices of dimension n×n. The suggested scheme provides a concurrent technique for users of symmetric‐key cipher systems to securely exchange their private keys over public channels. This protocol is shown to possess a high level of security based on the algorithm's parameters. We also present a scheme for generating pseudorandom numbers from a single chaotic map for use in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, Wang et al have shown that this scheme can be easily broken by using Parseval's theorem [17] . Recently, Almulla et al proposed a key exchange protocol where the platform group is a set of m commuting square singular matrices of dimension n × n over a finite field [18] . Almulla's scheme uses similar technique, in terms of the compositions of functions, as suggested in Ref [16], the selected set of square singular matrices instead of functions makes the scheme secure against various cryptanalytic attacks including that proposed in Ref [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, Wang et al have shown that this scheme can be easily broken by using Parseval's theorem [17] . Recently, Almulla et al proposed a key exchange protocol where the platform group is a set of m commuting square singular matrices of dimension n × n over a finite field [18] . Almulla's scheme uses similar technique, in terms of the compositions of functions, as suggested in Ref [16], the selected set of square singular matrices instead of functions makes the scheme secure against various cryptanalytic attacks including that proposed in Ref [17].…”
Section: Introductionmentioning
confidence: 99%
“…Almulla et al . propose a cryptographic protocol for symmetric key exchange based on a set of m commutative square singular matrices of dimension n × n . The suggested scheme provides a concurrent technique for users of symmetric‐key cipher systems to securely exchange their private keys over public channels.…”
mentioning
confidence: 99%